1998
DOI: 10.1002/(sici)1097-4628(19980307)67:10<1827::aid-app16>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stability of intumescent chars

Abstract: Intumescent fire-retardant systems have been studied in detail from all points of view. However, all works passed around questions of mechanical stability of foamed chars produced during burning. In the present work, mechanical properties of intumescent chars has been discussed. Technique and method of such investigations have been supposed. It was supposed that mechanical stability of foamed chars correlates with high molecular fraction in char residue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 1 publication
(1 reference statement)
0
15
0
Order By: Relevance
“…At the same time, phosphorus components produced inorganic glass compounds that stopped the flame spread. Unfortunately, a mechanical characterization of the final residues was not been carried out by the same authors, even though this aspect is of fundamental importance for its protective role, as well pointed out in a note by Reshetnikov et al [68].…”
Section: Tablementioning
confidence: 99%
“…At the same time, phosphorus components produced inorganic glass compounds that stopped the flame spread. Unfortunately, a mechanical characterization of the final residues was not been carried out by the same authors, even though this aspect is of fundamental importance for its protective role, as well pointed out in a note by Reshetnikov et al [68].…”
Section: Tablementioning
confidence: 99%
“…They showed that the addition of silicone additives improves the strength of char and also both thermal and mechanical parameters are considered simultaneously for clear understanding of the destruction behavior of char; effective char formation depends on the surface profile and chemical properties of the substrates. 4547 Muller et al 48 investigated the mechanical (compression) resistance of char, derived from 30% APP filled polyurethane intumescent system, using different heating devices, such as rheometer furnace, mass loss calorimeter, tubular oven, and plate–plate rheometer. There is no significant change in strength of char with respect to the presence of flame, heating type (convective or radiative), and the quenching temperature, whereas the heating temperature and heating rate are crucial parameters, which affect the mechanical strength of the char.…”
Section: Test Methods and Characterization Of Intumescent Coatingsmentioning
confidence: 99%
“…Besides thermal insulation, one of the key properties of an intumescent coating is its mechanical stability . A mechanical test of the residue was performed at room temperature after the furnace test (Figure ).…”
Section: Methodsmentioning
confidence: 99%